An IDP Policy for Afghanistan: from draft to reality - Wiseberg, L (Refugee Studies Centre, University of Oxford, 2014)
Developing a national policy to address the needs of Afghanistan’s IDPs was beset with obstacles and challenges. Although the IDP Policy is now a reality, its implementation is likely to meet challenges of a similar nature.